Peran Komunikasi yang Efektif sebagai Kunci menuju Kesuksesan Seorang Putri Juniawan - Raihany Nur Zahra; Nina Yuliana (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Communication is the most important key to building good relationships with each other. Effective communication relies heavily on an individual's skills in sending and receiving messages. Effective communication is an activity of conveying meaning (message) from one person to another, and this activity is mutually beneficial. Effective communication is a problem faced by Indonesian society today. They are not yet accustomed to an effective communication culture and lack the ability to listen in communication, so they often express their opinions to solve problems rather than having opinions to solve them. This research used a qualitative descriptive research method and also conducted interviews with resource persons. In this research, the researcher took the example of a successful communicator in her field, namely a junior daughter. Putri Juniawan is now someone who is successful in her career. By relying on his courage and public speaking, he was able to establish very extensive relationships with several companies. Active listening ability refers to an active comprehension process to obtain information and the speaker's attitude, the aim of which is to understand the conversation objectively.